Novel surface-enhanced raman scattering substrate based on functionalized silicon nanowires - Mahmood, Iram; Ahmad, Ishaq; Ahmad, Ishfaq (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study reports synthesis of a new Surface-Enhanced Raman Scattering (SERS) substrate using Silicon nanowires (SiNW’s) arrays, produced through chemical etching, and functionalized by tailoring their surface chemistry with nitrogen containing groups. From SEM characterization, phenomenon of micro channel formation, porosity and amorphous nature for the as prepared SiNWs was observed. Photoluminescence (PL) spectrum showed that these nanowires have broad emission band in the range of 500-900 nm. Also, change in the surface chemistry of Si nanowires after nitrogen treatment was observed by elemental analysis, EDX and X-ray photoelectron spectroscopy. The data showed that raising the modification temperature also increased the nitrogen content. At high temperature, pyridine and aromatic amines were the dominant functional groups while a small amount of quaternary nitrogen and protonated amide were also present. Methylene blue (MB) was used as a probe molecule to investigate SERS activities of functionalized SiNWs. The enhancement factor was estimated to be 107-109. Interaction of nitrogen containing groups on the surface of SiNWs with MB molecules resulted in high adsorption of MB on the substrate and higher signal detection by SERS.